2019
DOI: 10.1002/jsfa.9978
|View full text |Cite
|
Sign up to set email alerts
|

Binding characteristics of polyphenols as milk plasmin inhibitors

Abstract: BACKGROUND The potential use of polyphenols to improve the functional characteristics of dairy products has gained much attention. However, the effects of the polyphenols on naturally occurring enzymes in milk have not been studied extensively. Excess plasmin activity in dairy products might result in several quality defects. The objective of this study was to assess the ability of polyphenols to inhibit plasmin in milk using a molecular and kinetic approach. RESULTS Epicatechin gallate (ECG), epigallocatechin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…The ability of using enzymes with pomaces faces another hurdle that emerges from the unique ability of pomace bioactives [including polyphenols and tannins (Hemingway and Laks, 2012)] at certain concentration to influence (or even inactivate) the functionality of used enzymatic preparations either through specific or non-specific interactions (Martinez-Gonzalez et al, 2017;Yildirim-Elikoglu and Vural, 2019). Many reports showed the ability of certain polyphenolics to negatively influence the functions of natural or industrial enzymes in a similar fashion to their ability to negatively impact microbial growths (Gonçalves and Romano, 2017;Ramos-Pineda et al, 2019).…”
Section: Advantages and Disadvantages Of Enzyme-assisted Bioconversio...mentioning
confidence: 99%
“…The ability of using enzymes with pomaces faces another hurdle that emerges from the unique ability of pomace bioactives [including polyphenols and tannins (Hemingway and Laks, 2012)] at certain concentration to influence (or even inactivate) the functionality of used enzymatic preparations either through specific or non-specific interactions (Martinez-Gonzalez et al, 2017;Yildirim-Elikoglu and Vural, 2019). Many reports showed the ability of certain polyphenolics to negatively influence the functions of natural or industrial enzymes in a similar fashion to their ability to negatively impact microbial growths (Gonçalves and Romano, 2017;Ramos-Pineda et al, 2019).…”
Section: Advantages and Disadvantages Of Enzyme-assisted Bioconversio...mentioning
confidence: 99%
“…9 Furthermore, polyphenols have been reported as inhibitors of milk plasmin activity. 10 Most of the currently effective plasmin inhibitors primarily focused on clinical studies. 11 Ersoz and Dudak 12 developed a novel peptide inhibitor for plasmin based on the phage display technique, marking the first exploration of peptides as milk plasmin inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been demonstrated that legume protease inhibitors have potential in reducing the proteolytic activity of plasmin . Furthermore, polyphenols have been reported as inhibitors of milk plasmin activity . Most of the currently effective plasmin inhibitors primarily focused on clinical studies .…”
Section: Introductionmentioning
confidence: 99%